The 'present-tense' experience of failure in the university: Reflections from an action research project. (November 2020) - Whittle, Rebecca; Brewster, Liz; Medd, Will; Simmons, Hilary; Young, Rob; Graham, Edith
Abstract: This article reflects on insights from an action research project where we worked with students whose university experience was inhibited by the fear of failure. In contrast to the popular concept of 'learning from failure', which involves intellectualizing the experience and distancing ourselves from it, our findings demonstrate the importance of a 'present tense' focus on emotions and affects in order to understand the experience of failure for students. Doing so brings us face-to-face with the often painful experience of failure in the present moment which, we argue, is an important and valid part of the university experience. We conclude by reflecting on the kinds of spaces and skills that may be needed to work with this new understanding of failure and show that developing these is a crucial part of resisting neoliberalism and creating a more 'care-full' (Mountz et al., 2015) academy. Highlights: Fear of failure is an intense affectual experience which many students encounter. It is vital to engage with the lived experience of failure in the present tense. Neoliberalism can be countered by creating new skills and spaces for working with failure.